2016
DOI: 10.5539/gjhs.v9n6p151
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Questionnaire of Commitment to Exercise

Abstract: The present study aimed to make and establish psychometric features of an exercise commitment questionnaire. The primary 35 questions were administered to 210 staffs working in Isfahan Steel Company, 120 males and 90 females. Subjects had 10 years of work experience in the company and were randomly selected using stratified sampling method. Principle component analysis and Varimax rotation were used to measure its construct validity. Finally, 25 questions were extracted with more than 0.5 loading factor indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The Cronbach's alpha obtained was 0.873: this validated the reliability of the questionnaire by using internal consistency. This, in turn, generally indicated that the commitment-to-exercise questionnaire with satisfactory reliability and validity indices can be used as a suitable instrument for evaluation of commitment to exercise by psychologists and counselors in cognitive-behavioral interventions (Derakhshanpoor, Vaez Mousavi, & Taheri, 2016).…”
Section: Toolsmentioning
confidence: 88%
“…The Cronbach's alpha obtained was 0.873: this validated the reliability of the questionnaire by using internal consistency. This, in turn, generally indicated that the commitment-to-exercise questionnaire with satisfactory reliability and validity indices can be used as a suitable instrument for evaluation of commitment to exercise by psychologists and counselors in cognitive-behavioral interventions (Derakhshanpoor, Vaez Mousavi, & Taheri, 2016).…”
Section: Toolsmentioning
confidence: 88%